Un paisatge amb figures: a propòsit del patronímic Ioannes en la nissaga dels Macip. - ORTS, ALBERT FERRER (Scripta)
Joan Vicent Macip, better known as Joan de Joanes, was the most prominent of the three generations of Macips dedicated to pictorial needs. To such an extent that his name derives from a Latinized patronymic (Ioannes), from which his wife, his children and his granddaughter benefited. An alias that, subsequently, was used in the Valencian and Castilian version with the formula Joanes/Joan de Joanes or Juanes/Juan de Juanes until today. The present work investigates the vicissitudes of this evolution and, at the same time, the place where our protagonist was born, an imprecise fact that we now outline in accordance with the consulted documentation.